Arbeit mit Metaphern: Seelsorge als Praxis des Metaphorisierens - Dietz, Alexander (Wege zum Menschen, 2025)
A process perspective on metaphorical sense-making in interactions of pastoral care is described. Based on the analysis of various conversation excerpts, the meaning of multimodal metaphorizations in pastoral conversations is elaborated in dialogue with theoretical concepts on metaphor.